PENGAMANAN SISTEM INFORMASI PENGGUNA PADA APLIKASI GRANT ME MENGGUNAKAN ANDVANCED ENCRYPTION STANDARD: SECURING USER INFORMATION SYSTEMS IN GRANT ME APPLICATIONS USING ANDVANCED ENCRYPTION STANDARD - Aulyah Zakilah Ifani; Akbar Abdurrahman Jafaruddin; Antika Diana Liku; Indriani Indriani (LPPM Universitas Abdurrab, 2024)
Education has an important role in ensuring the survival of the nation and state, as well as improving the quality of human resources to participate in national development. Today's developing technology, including in the field of education, can make it easier for students to learn new things and get information, including about scholarship programs. However, the security of scholarship recipient data needs to be considered so that it is not easily accessed by unauthorized people. Cryptography can be an appropriate approach to secure such data. This research aims to secure Grant Me application user information using the AES algorithm to encrypt the username and password of scholarship recipients and scholarship providers. The method used is experimental testing of the system to be built using the AES algorithm. The results showed that the application of the AES algorithm with a key value of 256 bytes proved that user login information was not easy to know from either the application owner or a third party. With the application of AES as a security system, it can be concluded that the application becomes more secure from hacker interference.